The Role Of The Party In The System Of Democracy And Its Influence On Rights And Freedoms - Taxmina Abdullayeva Baxtiyarovna (Genius Journals, 2024)
This article provides a comprehensive analysis of the role of political parties in a democratic system and the process of ensuring the rights and freedoms of citizens through them. In democratic systems, parties are an important component of political life, which contribute to the formation of civil society by representing the interests of the people, ensuring competition in elections, and influencing state governance. The article also examines the positive and negative aspects of political parties. On the one hand, parties serve as a means of protecting the rights and freedoms of citizens, making the voices of different social strata of society heard, and developing political pluralism. On the other hand, it is considered that in some cases, parties can abuse their powers, show a tendency to authoritarianism, and create the risk of corruption and political manipulation
Keywords: political parties; democracy; civil society